Dissemination of Ceftriaxone-Resistant Salmonella Enteritidis Harboring Plasmids Encoding blaCTX-M-55 or blaCTX-M-14 Gene in China - Siyuan Yang; Jianzhong Fan; Lifei Yu; Jintao He; Linghong Zhang; Yunsong Yu; Xiaoting Hua (MDPI AG, 2024)
Salmonella Enteritidis was the primary foodborne pathogen responsible for acute gastroenteritis. The growing ceftriaxone resistance poses a significant threat to public health. Infection with S. Enteritidis has emerged as a major public health concern, particularly in developing countries. However, research on ceftriaxone-resistant S. Enteritidis (CRO-RSE) remains limited, particularly concerning its resistance mechanism, plasmid structure, and transmission characteristics. This study aims to address these gaps comprehensively. We collected 235 S. Enteritidis isolates from Hangzhou First People's Hospital between 2010 and 2020. Among these, 8.51% (20/235) exhibited resistance to ceftriaxone. Whole-genome analysis revealed that 20 CRO-RSE isolates harbored blaCTX-M-55 or blaCTX-M-14 on the plasmid. Moreover, the dissemination of the blaCTX-M-type gene was associated with IS26 and ISEcp1. Plasmid fusion entailing the integration of the p1 plasmid with antibiotic resistance genes and the p2 (pSEV) virulence plasmid was observed in certain CRO-RSE. Additionally, the structural analysis of the plasmids unveiled two types carrying the blaCTX-M-type gene: type A with multiple replicons and type B with IncI1 (Alpha) replicon. Type B plasmids exhibited superior adaptability and stability compared to type A plasmids within Enterobacteriaceae. Interestingly, although the type B (S808-p1) plasmid displayed the potential to spread to Acinetobacter baumannii, it failed to maintain stability in this species.